E-learning multidisciplinary developmental environment based on new European research paradigm - Njoo, Jim; Sergeyeva, Tetyana; Turlakova, Natalya (My University, 2023)
The research raises the problem of improving strategies, technologies, methods, techniques and tools of e-learning in connection with the change in the research paradigm, which will inevitably affect the education paradigm. Modern education, in fact, develops agents of changes who are called upon to maintain and develop the viability of society in the face of systemic economic, social and environmental crises. Therefore, goal-oriented science and education are gradually being transformed into impact-oriented, with the introduction of social, moral, economic, environmental and security criteria. The New European Bauhaus initiative is the quintessence of modern trends in the development of an advanced society, as a human-centered and aimed at human wellbeing through the formation of a sustainable-enriching-inclusive environment. The scale and speed at which changes are taking place require a new approach to students’ development. They must respond quickly to changes and use a challenge as an opportunity for development. Within the framework proposed by the authors, the eco-humanistic approach to human-environment interaction respond to new demands and can be integrated into e-learning multidisciplinary developmental environment, which simulates the real conditions of self-development in an ambiguous situation. The metacognitive approach as well as tailor-made and fit for purpose innovations make it possible to consciously manage the process of one's own development depending on individual conditions and needs. Modeling real work and life developmental environment demands multidisciplinary and multi-actor approaches for co-creation of efficient e-courses of a new generation. The authors propose an innovative strategies, techniques and tools for providing efficiency of e-courses.
Keywords: e-learning; pedagogical activity; digitalization; modern education; information technology